Enforcing GLUT3 expression in CD8+ T cells improves fitness and tumor control by promoting glucose uptake and energy storage - Cribioli, Elisabetta; Giordano Attianese, Greta Maria Paola; Ginefra, Pierpaolo; Signorino-Gelo, Amandine; Vuillefroy de Silly, Romain; Vannini, Nicola; Hess, Christoph; Irving, Melita; Coukos, George (Frontiers in Immunology, 2022)
Despite the tremendous success of adoptive T-cell therapies (ACT) in fighting certain hematologic malignancies, not all patients respond, a proportion experience relapse, and effective ACT of most solid tumors remains elusive. In order to improve responses to ACT suppressive barriers in the solid tumor microenvironment (TME) including insufficient nutrient availability must be overcome. Here we explored how enforced expression of the high-affinity glucose transporter GLUT3 impacted tumor-directed T cells. Overexpression of GLUT3 in primary murine CD8+ T cells enhanced glucose uptake and increased glycogen and fatty acid storage, and was associated with increased mitochondrial fitness, reduced ROS levels, higher abundance of the anti-apoptotic protein MCL-1, and better resistance to stress. Importantly, GLUT3-OT1 T cells conferred superior control of B16-OVA melanoma tumors and, in this same model, significantly improved survival. Moreover, a proportion of treated mice were cured and protected from re-challenge, indicative of long-term T cell persistence and memory formation. Enforcing expression of GLUT3 is thus a promising strategy to improve metabolic fitness and sustaining CD8+ T cell effector function in the context of ACT.